EDICIÓN CRÍTICA DE UNA OBRA INÉDITA DE ESTEBAN DE GARIBAY: CENSURA SOBRE LA HISTORIA QUE GONZALO DE AYORA ESCRIBIÓ DE LAS COSAS DE LA CIUDAD DE ÁVILA (C. 1580) - Quirós Rosado, Roberto (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
In the present study we analyze an unpublished paper by chronicler Esteban de Garibay y Zamalloa (1533-1599), a rough copy about Epílogo de algunas cosas dignas de memoria pertenecientes a la yllustre e muy magnífica, e muy noble, e muy leal ciudad de Áuila (Salamanca, 1519), the pioneer corography by Captain Gonzalo de Ayora de Córdoba, a chronicler of Catholic Kings. Besides to study his critic contents, we exposed relationship between Garibay and the city of Ávila, so his life that his manuscripts works.
Keywords: Historiography; Corography; Censure; Critic edition; Document; Ávila; Garibay; Ayora